2008
DOI: 10.1007/s00268-007-9356-0
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Distal Splenorenal Shunt in Children with Portal Hypertension for the Treatment of Severe Thrombocytopenia and Leukopenia

Abstract: DSRS is an effective and reliable procedure for children with PH and is still useful for selected pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
0
17
0
2
Order By: Relevance
“…Although deficiencies in endothelial prostacyclin synthase [6], excess circulating endothelin-1 [7], and PA platelet aggregates [8] have been documented in POPH patients, the molecular mechanisms driving the pathogenesis of the disease remain unclear. One of the primary reasons that the pathophysiological mechanisms directing POPH is still unknown is that animal, and in particular, mouse models of disease have not been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Although deficiencies in endothelial prostacyclin synthase [6], excess circulating endothelin-1 [7], and PA platelet aggregates [8] have been documented in POPH patients, the molecular mechanisms driving the pathogenesis of the disease remain unclear. One of the primary reasons that the pathophysiological mechanisms directing POPH is still unknown is that animal, and in particular, mouse models of disease have not been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Previously Moon et al [25] reported the result of distal spleno-renal shunt (DSRS, Warren shunt) in 15 patients, showing DSRS is an effective and reliable procedure for children with portal hypertension and is still useful for selected pediatric patients. DSRS can be used as a bridge to LT if PHT is secondary to intrahepatic problems.…”
Section: Phtmentioning
confidence: 99%
“…Moreover, for these complications endoscopic treatments are clearly unsuitable [51]. In those cases, or when hemorrhagic episodes are refractory to other treatments, surgery becomes the only option [52]. …”
Section: Treatmentmentioning
confidence: 99%